2021
DOI: 10.3393/ac.2020.05.22
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Early Urinary Catheter Removal Integrated in the Full Enhanced Recovery After Surgery (ERAS) Protocol After Laparoscopic Mid to Lower Rectal Cancer Excision: A Feasibility Study

Abstract: Purpose: Enhanced Recovery After Surgery (ERAS) programs advocate early urinary catheter removal after rectal cancer surgery; however, the optimal duration remains unclear. This study assessed the feasibility of the early urinary catheter removal protocol after rectal cancer surgery within an ERAS pathway and identified predictive factors for failure of this strategy.Methods: Between March 2017 and October 2018, all unselected and consecutive patients who underwent rectal cancer resection and benefited from ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Early removal may be effective in reducing patient discomfort and facilitating early mobilization and prevention of urinary tract infection, but the risk of urinary retention is high. Others have suggested that the appropriate time to remove a urinary catheter is within 72 hours after surgery for rectal cancer [31][32][33]. We routinely attempted to remove the urinary catheter on POD3, but reinsertion was sometimes necessary because of urinary retention, depending on the patient's urological comorbidity or whether pelvic lateral lymph node dissection was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Early removal may be effective in reducing patient discomfort and facilitating early mobilization and prevention of urinary tract infection, but the risk of urinary retention is high. Others have suggested that the appropriate time to remove a urinary catheter is within 72 hours after surgery for rectal cancer [31][32][33]. We routinely attempted to remove the urinary catheter on POD3, but reinsertion was sometimes necessary because of urinary retention, depending on the patient's urological comorbidity or whether pelvic lateral lymph node dissection was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, enhanced recovery after surgery (ERAS) program has shown that early rehab and early feeding in postoperative patients are good prognostic factors for patients' recovery [ 110 111 112 113 114 115 ]. The ERAS program recommends catheter removal on postoperative day 1, but surgeons should be taken care when removing it due to the risk of nerve damage during rectal cancer surgery.…”
Section: How To Improve Surgical Outcomesmentioning
confidence: 99%
“…So, in addition to the ERAS program, the appropriate timing of catheterization should also be considered in patients with rectal cancer [ 116 117 118 ]. One study showed that the appropriate time for catheter removal was 3 days of postoperative day [ 111 ].…”
Section: How To Improve Surgical Outcomesmentioning
confidence: 99%
“…Regarding the timing of postoperative urinary catheter removal, the ERAS Society guidelines recommend 1-3 days after elective colorectal surgery, while the ASCRS guidelines recommend catheter removal within 24 hours for colon-upper rectal resection and within 24-48 hours after mid-lower rectal surgery. Meillat et al [26] reported the outcomes of Foley catheter removal on the third postoperative day in 135 patients who underwent surgery under the ERAS protocol, in accordance with the ERAS Society recommendation. This study found successful removal in 88.9% of cases, with risk factors for failure including obesity, an American Society of Anesthesiologists grade greater than II, anti-aggregation platelet medication, absence of anastomosis, and extended operation time.…”
Section: ) Other Ileus-prevention Itemsmentioning
confidence: 99%